A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘notoides’ clade to a new genus, Xipholeptos n. gen. - Reid, Amanda L.; Strugnell, Jan M. (Zootaxa, 2018)
A new species of pygmy squid, Idiosepius hallami n. sp., is described from eastern Australia. It differs from I. notoides Berry, 1921 and I. pygmaeus Steenstrup, 1881 (also found in Australian waters) in a number of traits, including the number of club suckers, shape of the funnel-mantle locking apparatus and the modification of the male hectocotylus. Mitochondrial DNA markers (12S rRNA, 16S rRNA and cytochrome c oxidase subunit 1) indicate that it is also distinct on a molecular level. The new Australian species is also recognised as the taxon from Stradbroke I., Queensland for which the entire mitochondrial genome has been sequenced (Hall et al. 2014). Idiosepius hallami n. sp. is compared with all nominal Idiosepius Steenstrup, 1881 and a current summary of Idiosepius systematics is provided as a basis for future studies. Based on our analyses, we propose the elevation of the ‘notoides’ clade to the new genus Xipholeptos n. gen., retaining Idiosepius as the genetic epithet for all other nominal idiosepiids. This is supported by: monophyly of the two lineages based on molecular data sets, the level of sequence divergence between these lineages, and morphological differences. The ‘notoides’ clade is endemic to southern Australia and its basal phylogenetic position suggests that the family may have originated in the Australasian region. Idiosepiids are found in seagrass beds and among mangroves—among the most threatened ecosystems in the world.